Penerapan Pra Literasi pada Anak Usia Dini di TK Fajar - Imas Masitoh; Noer Ayunda Novalinda; Pandu Aditya Ramadhani (Edu Happiness : Jurnal Ilmiah Perkembangan Anak Usia Dini, 2022)
Pre-literacy cultural learning needs to be instilled from an early age, because at that age children enter the golden period or often called the golden age. Early childhood is a child aged zero to six years, at that time children experience very rapid development and growth, so that the habits that children do from an early age will also become habits when they are adults. This research was conducted with a descriptive qualitative approach using literature study and interviews. The data obtained in the form of primary and secondary data, where the primary data obtained from the results of interviews with parents and teachers as well as the process of observing observations in the field. While secondary data obtained from previous research journals. From the results of research conducted at Fajar Pangandaran Kindergarten, it can be concluded that the majority of parents emphasize educational institutions to provide calistung or literacy learning to children, while many parents do not understand what literacy is and how to introduce pre-literacy to their children from an early age. But apart from that, at Fajar Kindergarten, certain methods of learning have been applied to efforts to apply pre-literacy to early childhood. Literacy from an early age is indeed important to be applied to children so that they are able to develop their cognitive aspects with basic knowledge for future provisions.